Eosinophils and Neutrophils Eliminate Migrating Strongyloides ratti Larvae at the Site of Infection in the Context of Extracellular DNA Trap Formation - Ehrens, Alexandra; Rüdiger, Nikolas; Heepmann, Lennart; Linnemann, Lara; Hartmann, Wiebke; Hübner, Marc P.; Breloer, Minka (Frontiers in Immunology, 2021)
Parasitic nematodes such as hookworms actively penetrate the skin of their hosts, encountering skin-resident innate immune cells that represent the host´s first line of defense. Here we use Strongyloides ratti as a model for an intestinal helminth parasite with tissue migrating stages. We show that interception and killing of migrating larvae in mice during a 1st infection occurred predominantly in skin and muscle tissue before larvae migrated via lung and head tissue to the intestine. Inhibition of larval migration was even more efficient in immune mice during a 2nd infection where larvae barely left the site of entry i.e. the foot. Using cell-deficient mice we show that interception in the tissue was predominantly mediated by neutrophils and eosinophils while basophils and mast cells were dispensable in vivo. Likewise, neutrophils and eosinophils inhibited S. ratti L3 motility in vitro in the context of ETosis. Thereby eosinophils were strictly dependent on the presence of anti-S. ratti antibodies while neutrophils inhibited L3 motility as such. Also, MPO and MMP-9 were released by neutrophils in response to L3 alone, but immune plasma further stimulated MPO release in an antibody-dependent manner. In summary, our findings highlight the central role of the skin as first line of defense against helminth parasites in both, innate and adaptive immunity.